Ivan Pavlov (1849-1936) dan Warisan Psikologi Eksperimental: dari Refleks Syaraf Hingga Pembentukan Perilaku - Ratnawati, Dwi Indah (Syntax Literate, 2026)
Ivan Pavlov is an important figure in experimental psychology who contributed to the theory of conditioned reflexes as the basis for understanding the learning process through stimulus-response associations. This paper comprehensively reviews Pavlov's biography, the social and scientific context of his time, and the main principles of his revolutionary theory. In addition, Pavlov's major contributions to the development of modern psychology are discussed, criticisms and controversies over his approach, as well as the relevance of his theories in contemporary psychology, particularly in behavioral therapy, education, and neuroscience. This paper aims to provide a thorough and critical understanding of Pavlov's scientific legacy that remains relevant and continues to be developed in various fields of psychology to the present and future.